Age Appropriate Childhood Immunization and Catch-up Immunization, Pakistan. - Saleem, Ali Faisal (Infectious Diseases Journal of Pakistan, 2023)
Childhood immunization save more than three million lives each year. In Pakistan, Expanded Program on Immunization (EPI) provides immunity against nine deadly diseases for infants and young children. An estimate of 19.4 million infants worldwide are still missing basic vaccines. One and a half million deaths could be avoided with improved global vaccination coverage. According to Pakistan Demographic and Health Surveillance (2012-13)1 report, only 43% of children received all vaccination by 12 months of age, however this reduced to 35% for Sindh.2 Sindh has 2,786 registered births who are under 5 years of age.3 Unfortunately, Pakistan has yet to know about the current figures or percentages of children who had missed their age appropriate vaccination.4 It is concerning not to know about alternative schedule that can be used to guide parents on catch-up immunization for missed children. Pakistan lacks an alternative schedule or catch-up immunization schedule for children under 2 years of age. To strengthen the efforts of health care team and betterment of community a catch-up immunization policy is also needed.5 Some important proximal determinants of low immunization in Pakistan are low literacy rate, lack of empowerment and involvement of women in decision making, higher fertility rates etc. Being afraid of side-effects of vaccines, vaccination phobia or surrounded by many anti-vaccine families or for many other reasons parents miss age appropriate vaccination of their children, however the same mind set is not prevalent in Pakistan. Lack of resources, information and advocacy are also some factors that had contributed towards under-utilization of vaccines against vaccine preventable diseases. This ultimately poses great risk to community; making vulnerable population more prone towards disastrous diseases.6 Under immunization has significantly shown to increase risk of contracting and spreading vaccine preventable diseases. Like Measles breakout in Pakistan; this all reminds Government to focus more on supplementary immunization activities (SIAs). To immunize children at an age when their immune response from the vaccine will be most effective, while still early enough to prevent them from contracting diseases when they are most susceptible.7 Deferring certain vaccinations, parents are putting their children at a far greater risk of deadly diseases; such as Measles, Pneumonia, and Pertussis.8 Parents also prefer to administer one vaccine or combination vaccines at a time, this also createsan area of research to work on developing combination vaccines.9 Introduction of new vaccine in immunization schedule is a historical moment for the country; currently introduced in Punjab and will be extended to other parts of Pakistan along with the support of WHO, UNICEF and GAVI.10 We need to focus on our efforts to help parents recognize the importance of timely vaccination, catch-up immunization schedule is safe for their children and help them understand that delay vaccination is only adding on their child’s risk. Challenges identified to get targeted result are quality and utilization of data, community involvement, availability of vaccines and better access to immunization services. Advertising is also an essential component to increase awareness of new vaccines and seriousness of a disease, to direct parents towards important source of information and to minimize misconception related to vaccine. At national level vaccination campaigns need strong integrated planning. Post vaccination campaign require much work to be done like timely accomplishment of vaccine campaigns, monitoring adverse reactions, and carrying out surveillance during and after campaign implementation. Continuous review of immunization schedules is necessary to stress upon significant issues of childhood immunization. At National level, there is urgent need to reinforce and strengthen the surveillance of VPDs.